2020
DOI: 10.1017/s1478951520000139
|View full text |Cite
|
Sign up to set email alerts
|

Dignity-conserving care for persons with palliative care needs — identifying outcomes studied in research: An integrative review

Abstract: Objectives. With people living longer, palliative care may be required for lengthier periods of time. This puts demands on healthcare organizations to provide optimal palliative care. Maintaining dignity is central for any person's health and quality of life, but especially for a person with palliative care needs. Dignity-conserving care needs to be evaluated to increase knowledge about outcomes and how to assess these. The purpose of this integrative review was to identify outcomes studied within dignity-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Little research has examined the impact of intimate dependency at the end of life as disease progresses and function declines 20 within the context of occupational adaptation. This study sought to understand how people with palliative care needs experience dignity with intimate hygiene as function declines and how they adapt to this increased dependence, examined against Model of Human Occupation constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Little research has examined the impact of intimate dependency at the end of life as disease progresses and function declines 20 within the context of occupational adaptation. This study sought to understand how people with palliative care needs experience dignity with intimate hygiene as function declines and how they adapt to this increased dependence, examined against Model of Human Occupation constructs.…”
Section: Introductionmentioning
confidence: 99%
“…9 Dignity-conserving approaches can help older persons feel respected 10 and HCPs can be guided in providing relevant palliative care. 11 Dignity interventions are rare, 12,13 and more research is needed to make them a solid part of older persons' health care. An integrated review 12 showed that dignity-conserving care (DCC) is often evaluated based on outcomes connected to illness-related concerns, but rarely based on dignity or social outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Good caring encounters can be seen as individual, person-to-person connections in which the interaction happens as equals (Wälivaara et al, 2013). Patients with life-threatening conditions need to be treated as unique and whole people, not just as a case of ‘diseases’ (Söderman et al, 2020). Healthcare professionals’ ethical awareness is needed to ensure successful encounters, quality of care (Akin Korhan et al, 2018) and possibilities for the patient to make autonomous decisions regarding their regular care, all of which requires frequent conversations with the healthcare professionals (Houska & Loučka, 2019; Nygren Zotterman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%